Storage stability and physical properties of asphalt modified with nanoclay and warm asphalt additives - Abdullah, Mohd Ezree (2011)
Asphalt is manufactured from crude oil and traditionally regarded as a colloidal system made up of asphaltenes micelles covered by a stabilizing phase of polar resins, which however, forms the interface with a continuous oily maltenic medium [1-3]. In spite of this traditional application, today only about 10% of asphalt is used as roofing material, for thermal and acoustic insulation, humidity and corrosion protection components of paints and varnishes, etc., while the remaining 90% is used for paving. Asphalt binder constitutes only a small but crucial part of any paving mix [4]. Physical properties and temperature susceptibility characteristics of the asphalt binder influence pavement performance at low and high field operating temperatures [5]. Recently, warm mix asphalt (WMA) has become popular where this technology allows reduction in fuel consumption and emissions in plants by addition of warm asphalt additive (WAA) [6-8]. During the ‘‘in life” service of asphalt binders, there are many types of failures, e.g. rutting, fatigue cracking and thermal cracking, which can reduce the quality and performance of pavements. Polymer modified asphalt (PMA) are blends of asphalt and one or more polymers, usually added in percentages ranging from 3% to 7% by weight, and were developed to overcome, or at least reduces, such problems. A various number of polymers have been used to produce PMA, but only a few are satisfactory from both the performance and the cost points of view [9]. Nowadays, researchers had put their interests on nanoclay which is a polymer that commonly used because it’s environmentally friendly and readily available. The proper selection of modified clay is essential to ensure effective penetration of the polymer into the interlayer spacing of the clay and so resulting in the desired exfoliated product [1, 5, 10- 11]. Literature review has shown few studies investigating the effects of nanoclay upon binder incorporating WAA. Prior to investigating the properties of nanoclay modified binders containing WAA, the modified binders with the additives need to be studied in detail. The main objective of this study was to evaluate the method of preparation and storage stability properties of nanoclay modified binders containing WAA.